2010
DOI: 10.1051/0004-6361/200913688
|View full text |Cite
|
Sign up to set email alerts
|

A MAD view of Trumpler 14

Abstract: We present adaptive optics (AO) near-infrared observations of the core of the Tr 14 cluster in the Carina region obtained with the ESO multi-conjugate AO demonstrator, MAD. Our campaign yields AO-corrected observations with an image quality of about 0.2 across the 2 field of view, which is the widest AO mosaic ever obtained. We detected almost 2000 sources spanning a dynamic range of 10 mag. The pre-main sequence (PMS) locus in the colour−magnitude diagram is well reproduced by Palla & Stahler isochrones with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 26 publications
11
87
5
Order By: Relevance
“…The present results from the M 17 region seem to be corroborated by the multiplicity properties of Tr14, a dense young cluster (<1 Myr, Sana et al 2010) in the Carina nebula. Though it has only six O stars with RV information (Sana & Evans 2011), none of them has been detected as a short-period binary (though see Maíz Apellániz et al 2017, for HD 93129A).…”
Section: Discussionsupporting
confidence: 83%
“…The present results from the M 17 region seem to be corroborated by the multiplicity properties of Tr14, a dense young cluster (<1 Myr, Sana et al 2010) in the Carina nebula. Though it has only six O stars with RV information (Sana & Evans 2011), none of them has been detected as a short-period binary (though see Maíz Apellániz et al 2017, for HD 93129A).…”
Section: Discussionsupporting
confidence: 83%
“…This effect is, however, mainly restricted to the extremely dense cluster Tr 14 near the center of the Carina Nebula, where the very strong source crowding leads to considerable incompleteness of the VISTA catalog. Observations with much better angular resolution are required for detailed studies of such dense clusters; for Tr 14, we note that results of adaptive-optics observations have been presented by Ascenso et al (2007) and Sana et al (2010).…”
Section: Detection Efficiencymentioning
confidence: 93%
“…These two studies are mostly limited to the northern hemisphere and are thus missing some of the richer massive star clusters and associations in the southern sky. Part of this gap is filled by the AO campaigns of Duchêne et al (2001) and Sana et al (2010b) on, respectively, NGC 6611 and Tr 14. Both studies revealed a lower multiplicity fraction of 18% for their sample of OB stars.…”
Section: Spectroscopic Binary Fraction In Various Separation Regimesmentioning
confidence: 99%
“…In these environments, disentangling the true pairs from chance alignment with stars in the same clusters becomes more challenging and only a smaller separation range can be investigated reliably. Interestingly, both Duchêne et al (2001) and Sana et al (2010b) concluded that OB stars have more companions than lower mass-stars.…”
Section: Spectroscopic Binary Fraction In Various Separation Regimesmentioning
confidence: 99%